PEMASARAN PRODUK-PRODUK UKM PIK (PUSAT/PERKAMPUNGAN INDUSTRI KECIL) PULOGADUNG1 - Sukarna Wiranta (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
Small businesses in Indonesia have a critical role in national economy, judging from the number of companies and workers involved in the business. Based on the data from the Board of Statistics (CBS) in 2006, has shown that small and medium businesses in Indonesia were 48.9 million principal or 99.9 percent of total business. The number of workers involved in small business was recorded about 50 million or 90 percent of the total employed by 2010. This study aims to evaluate the performances of small scale industries in PIK Pulogadung which uses criteria of effectiveness and efficiency of its owners/managers of the company. Based on the study, most of the respondents where classified as the traders (90%), while the crafter is only 5%. Thus, the PIK is likely the market of textiles and products of textiles (TPT), and footwear products. However, the channel distribution mostly directly from producer to consumers, although there were used big retailer network.